Back Cover: Breslow Intermediates from Aromatic N‐Heterocyclic Carbenes (Benzimidazolin‐2‐ylidenes, Thiazolin‐2‐ylidenes) (Angew. Chem. Int. Ed. 27/2018). Issue 27 (7th June 2018) - Paul, Mathias; Sudkaow, Panyapon; Wessels, Alina; Schlörer, Nils E.; Neudörfl, Jörg‐M.; Berkessel, Albrecht
Abstract : Breslow intermediates are the mechanistic heart of thiamine catalysis in vitamin B1‐dependent enzymes, such as pyruvate decarboxylase. In their Communication on page 8310 ff., A. Berkessel and co‐workers present the first NMR characterization of a thiamine‐related Breslow intermediate featuring the biologically and organocatalytically relevant aromatic thiazole heterocycle, together with NMR and X‐ray characterization of benzimidazole‐derived Breslow intermediates (cover picture: Adrian von der Höh).